Rendészeti szervek a biztonsági kihívásokkal összefüggésben, az információáramlás tükrében - Csege Gyula (Egyesület Közép-Európa Kutatására, Szegedi Tudományegyetem Juhász Gyula Pedagógusképző Kar, 2019)
In recent decades, policing has undergone major changes, with changes and expansion of the private sector and social needs, the reorganization of national security services and law enforcement agencies to a large extent affecting security levels. My goal is to present the actors of private security and national security and the needs caused by social and security challenges, along with the security phenomena that accompany our day, such as change in law enforcement, terrorism, migration, and certain aspects of cyberspace in relation to information flow issues.